The French Tax on Air Pollution: Some Preliminary Results on its Effectiveness - Katrin Millock; Céline Nauges (Fondazione Eni Enrico Mattei (FEEM), 2003)
Empirical evidence evaluating the efficiency of economic instruments is still rare, despite significant theoretical advances over the last decades. The objective of this paper is to evaluate one form of environmental taxation, the French tax on air pollution from 1990-99. While starting out in 1985 as a tax levied only on emissions of sulphur dioxide (SO2 ), the tax base was subsequently extended to encompass also emissions of nitrogen oxides (NOx), hydrochloric acid (HCl), and volatile organic compounds (VOC). The revenues of the French tax on air pollution were earmarked for abatement subsidies and the financing of air quality surveillance systems. Using a plant-level database, we find a negative, significant effect of the tax on emissions of SO2, NOx, and HCl. The abatement elasticity with regard to the tax is quite small, however.
Keywords: H00; H23; Q25; Q28; 330; Environmental tax; emissions regulation; earmarking; air quality; Ökosteuer; Luftverschmutzung; Sondersteuer; Frankreich